2000
DOI: 10.1258/002367700780384744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various levels of dietary Artemisia abyssinica leaves on rats

Abstract: Artemisia abyssinica leaves, a traditional medicine for the treatment of various disorders, were fed to male Wistar rats at 2% and 10% of the standard diet for 6 weeks. A 2% A. abyssinica leaf diet was not toxic to rats. Depression in growth, hepatopathy and nephropathy were observed in rats fed a diet containing 10% of A. abyssinica leaves. These findings were accompanied by leukopenia, anaemia and alterations of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and gamma glutamyl transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…As the liver is the organ that protects the individual against toxic injury, it seems that the dose of F. vulgare given to mice in this study exceeded the capacity of the liver to repair the damage. Many authors reported that toxic plants have induced similar liver damage in different animal species [25] [26] [27] [28]. The results of the present study have also revealed that F. vulgare induced toxic damage in kidney tissues.…”
Section: Discussionsupporting
confidence: 79%
“…As the liver is the organ that protects the individual against toxic injury, it seems that the dose of F. vulgare given to mice in this study exceeded the capacity of the liver to repair the damage. Many authors reported that toxic plants have induced similar liver damage in different animal species [25] [26] [27] [28]. The results of the present study have also revealed that F. vulgare induced toxic damage in kidney tissues.…”
Section: Discussionsupporting
confidence: 79%
“…The essential oil of A. absinthium originating from different countries has been the subject of previous investigations and different chemotypes were reported in literature [3][4][5][6][7][8]12]. Four chemotypes were identified to be characteristic of A. absinthium grown in Europe: sabinene and myrcene rich oil, α-and β-thujone rich oil, epoxyocimene rich oil, and (E)-sabinyl acetate rich oil.…”
Section: Resultsmentioning
confidence: 99%
“…Bip., A. herba-alba Asso., A. judaica L. and A. monosperma Del. are used in folk medicine as anthelmintics, antispasmodics, antirheumatics and antibacterial agents due to the presence of alkaloids, flavonoids, sterols, tannins, volatile oils and anthraquinones [7].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to induction of CYP450 enzyme. Adam et al (2000), also reported the presence of alkaloids, flavonoids, sterols, tannins, volatile oils and anthraquinones in aerial parts of the Artemisia species. These compounds were considered according to findings of Iriadam et al (2006) ▶ for detoxification of organs.…”
Section: Introductionmentioning
confidence: 98%